2022
DOI: 10.3389/fonc.2022.801230
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing Radiation-Induced GDF15 Promotes Angiogenesis in Human Glioblastoma Models by Promoting VEGFA Expression Through p-MAPK1/SP1 Signaling

Abstract: Glioblastoma multiforme (GBM), the most aggressive cancer type that has a poor prognosis, is characterized by enhanced and aberrant angiogenesis. In addition to surgical resection and chemotherapy, radiotherapy is commonly used to treat GBM. However, radiation-induced angiogenesis in GBM remains unexplored. This study examined the role of radiation-induced growth/differentiation factor-15 (GDF15) in regulating tumor angiogenesis by promoting intercellular cross-talk between brain endothelial cells (ECs) and gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
(40 reference statements)
1
9
0
Order By: Relevance
“…Angiogenesis was not only required for tumor growth but also required for tumor dissemination [30,31]. Many studies have reported that traditional photon radiotherapy can activate tumor angiogenesis, besides its capability in killing the tumor cells [7,32]. However, patients who received carbon ion radiotherapy were reported to have decreased metastasis and recurrence rates [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…Angiogenesis was not only required for tumor growth but also required for tumor dissemination [30,31]. Many studies have reported that traditional photon radiotherapy can activate tumor angiogenesis, besides its capability in killing the tumor cells [7,32]. However, patients who received carbon ion radiotherapy were reported to have decreased metastasis and recurrence rates [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…It is abundantly expressed in the placenta during physiological conditions and secreted by activated macrophages as a response to cellular stress signals, such as inflammation, tissue injury and hypoxia ( 23 ); its effect is to stimulate proliferation and migration of endothelial colony-forming cells ( 24 ). GDF15 exerts its pro-angiogenic effects at least partly by stimulation of VEGF-A synthesis ( 25 ). Increased levels of circulating GDF15 are seen in patients with various types of cancer including myeloproliferative neoplasms and in multiple myeloma increased GDF15 is associated with poor prognosis ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with our results, which showed a regulation of GDF15 expression by IR in the GSCs, it was previously published that IR could also induce the expression and secretion of this cytokine in oral carcinoma cells [ 34 , 35 ]. Similarly, it was shown that IR regulates GDF15 expression by cells in the tumor microenvironment, including macrophages, fibroblasts, or endothelial cells [ 11 , 36 , 37 ]. In particular, GDF15 secretion by irradiated endothelial cells has been shown to contribute to angiogenesis in GBM models [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it was shown that IR regulates GDF15 expression by cells in the tumor microenvironment, including macrophages, fibroblasts, or endothelial cells [ 11 , 36 , 37 ]. In particular, GDF15 secretion by irradiated endothelial cells has been shown to contribute to angiogenesis in GBM models [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation